Composition and natural history of the snake community in a preserved forest in Central Amazonia, Pará, Brazil - Galúcio da Frota, Jossehan (2021)
We present information about a snake community in a preserved forest in central Amazonia and describe the composition, habitat use, daily activity, diet, and reproduction. The study area is mainly in the municipality of Itaituba in Parque Nacional da Amazônia, state of Pará, Brazil. We set up 26 plots along of a 135 km on a stretch of the BR-230 highway. We used three quantifiable capture methods: Time Constrained Visual Search (TCS), Road Search by Car (RS) and Pitfall Traps with drift fence (PTS). We also recorded all snakes eventually found by the team outside the collection protocol (occasional encounters) and those obtained by other people (third-party encounters). Reproductive (sexual dimorphism, reproductive maturity, recruitment, and fecundity), and feeding biology (diet composition and frequency of food items) are presented. We recorded 61 species from 38 genera and seven families. Imantodes cenchoa, Helicops angulatus, and Bothrops atrox were the most abundant species. Most species have terrestrial habits and nocturnal activity. The most consumed prey was lizards and frogs. Observing the number of specimens distributed monthly, we noted that most specimens with eggs and embryos were recorded in the dry season, while births occurred throughout the year. Compared to some snake communities located south and north of the Amazon River, the snake community of Parque Nacional da Amazônia has high species diversity, resulting from the presence of different lineages as well as different functional groups, which reflect past and present events that have occurred in this region.